ARQ Protocols for Two-Way Wireless Relay Systems: Design and Performance Analysis. (21st June 2012) - Chen, Zhenyuan; Gong, Qiushi; Zhang, Chao; Wei, Guo
Abstract : Two-way relay (TWR) communication, a new cooperation paradigm that allows two terminals to share one relay node to communicate with each other in two phases, has played an increasingly valuable role in wireless networks to meet the stringent throughput requirement. In this paper, we focus on the designing of automatic repeat-request (ARQ) protocols for the two-way wireless relay systems. According to different feedback schedules, we propose three basic ARQ protocols to improve the throughput of two-way relay systems, namely, relay-only ARQ (Ro-ARQ), terminal only ARQ (To-ARQ) and relay-terminal ARQ (RT-ARQ). Through analyzing the outage throughput of these three ARQ protocols, it is verified that all three protocols can improve the system performance. In addition, simulation results reveal that the RT-ARQ protocol has the closest performance to the theoretical throughput upperbound among all given methods without severe deterioration on system complexity.